Comparison of oviposition preference of black soldier fly (Hermetia illucens) on different substrate as egg laying attractant - Anggia, Rachel; Putra, Ramadhani Eka (Jurnal Biologi Udayana, 2021)
Black soldier fly ( Hermetia illucens ) is one of the biological agents for organic waste decomposition. This process produced insect biomass with significant economic value. To maintain the population of this insect, an artificial rearing had to be done to produce a continuous supply of eggs. One of the important components of egg production is substrate to attract female to lay egg on the ovitraps. Ovitrap is a structure applied to accumulate the egg for easier handling. In this study, the preference of female on the several types of attractants was tested. The subtrates were rotten cabbage, rotten papaya, tofu dreg, and commercial fish feed. The preference was based on the amounts of eggs laid on the ovitrap (in weight). The result showed that fish mill is the most preference substrate (amount of eggs: 2.17 gram) while tofu dreg was the least preferred substrate (amount of eggs: 0.06 gram).